Methane displacement characteristic of coal and its pore change in water injection. Issue 5 (September 2020) - Chen, Xuexi; Shan, Wenxuan; Sun, Ruibang; Zhang, Liang
Coalbed methane as one type of clean energy has become an important gas resource recently. High-pressure water injection in coal seams is an effective approach for improving gas extraction efficiency, which is determined by the gas displacement characteristic and pore structure of coal. To investigate the gas displacement characteristics in coal and its pore response and influential factors, gas adsorption and water injection experiments were conducted under different conditions. The results show that the gas displacement caused by the water injection undergoes three stages: rapid increase, slow increase, and almost constant. The wetting process in water injection includes three processes: wetting, soaking, and spreading, and the wettability of coking coal is best, followed by lean coal and anthracite. The amount of gas driven by the water increases with increasing water injection pressure, and it is more favorable to increase the injection pressure to improve the gas displacement effect under the relatively low injection pressure. The lower the coal rank, the better the gas displacement effect due to the higher porosity of the coal, and the longer the early gas displacement stage. The high adsorption equilibrium pressure can improve the gas displacement effect; for the relatively high adsorption equilibrium pressure, the gas displacement effect is better. After water injection in coal, the large fractures and pores dramatically increase in size, especially for the low metamorphic coals coking coal, contributing to the majority of the increase in porosity. The results of this study can provide a theoretical foundation for the wide application of water injection technology for efficient gas drainage in coal mines.